General overview on the study of Islamic ethics - Abdul Rahim, Adibah (IIUM Press, International islamic University Malaysia, 2014)
This chapter attempts to clarify the definition of ethics including its two categories of scientific and philosophical studies. It also explains how Islamic ethics and its scope have been defined by different Muslim scholars. In addition,it highlights few sources of Islamic ethics, namely, Qur'an and Sunnah, Islamic theology, Islamic philosophy, Islamic jurisprudence, and Islamic mysticism. This chapter also explains how Islam gives very much emphasis on the importance of ethics and its significance for the development of individual and society. In doing so, few Quranic verses and ahadith have been highlighted in order to support the argument. The author tries to present ethics as the counter part of other sciences, such as, law, politics, science, economics, and others for such sciences become soulless or insignificant if detached from ethics. This chapter also highlights how Islamic ethics has been developed and treated systematically by Muslim scholars like Miskawayh and al Ghazzali. The chapter then identifies few characteristics of Islamic ethics which distinguished it from Christian and Jewish ethics. General overview on Islamic ethics in relation to the concept of iman, islam, and ihsan is also highlighted. The last part of the chapter discusses about the relationship between Islamic ethics and the shari'ah. The emphasis was given on the similarity of their objectives, that is, to regulate the relationship of man with god, and man with man. Thus, both the shari'ah and Islamic ethics cannot be separated from each other.